2016
DOI: 10.1002/hipo.22657
|View full text |Cite|
|
Sign up to set email alerts
|

3‐Hz subthreshold oscillations of CA2 neurons In vivo

Abstract: The CA2 region is unique in the hippocampus; it receives direct synaptic innervations from several hypothalamic nuclei and expresses various receptors of neuromodulators, including adenosine, vasopressin, and oxytocin. Furthermore, the CA2 region may have distinct brain functions, such as the control of instinctive and social behaviors; however, little is known about the dynamics of the subthreshold membrane potentials of CA2 neurons in vivo. We conducted whole-cell current-clamp recordings from CA2 pyramidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…We found that during spontaneous theta activity, the peak and reversal of membrane potential oscillations shifted in phase, consistent with different phase-locking preferences at proximal and distal sectors. Other report also noted different theta modulation in pyramidal cells recorded around CA2 in mouse, but neurochemical confirmation was not available (Matsumoto et al, 2016). Two independent analyses provided additional support to this functional segregation along the transverse axis.…”
Section: Discussionmentioning
confidence: 86%
“…We found that during spontaneous theta activity, the peak and reversal of membrane potential oscillations shifted in phase, consistent with different phase-locking preferences at proximal and distal sectors. Other report also noted different theta modulation in pyramidal cells recorded around CA2 in mouse, but neurochemical confirmation was not available (Matsumoto et al, 2016). Two independent analyses provided additional support to this functional segregation along the transverse axis.…”
Section: Discussionmentioning
confidence: 86%
“…We found that during spontaneous theta activity, the peak and reversal of membrane potential oscillations shifted in phase, consistent with different phase-locking preferences at proximal and distal sectors. Other report also noted different theta modulation in pyramidal cells recorded around CA2 in mouse, but neurochemical confirmation was not available (Matsumoto et al., 2016). Three independent analyses provided additional support to this functional distribution along the transverse axis.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, the analysis of membrane potential dynamics of identified cells from the DG to CA1 suggests striking regional organization across the proximodistal and deep-superficial axes both in awake and anesthetized conditions ( Table 3 ). During SWR under urethane, neuronal activity runs as an avalanche from the proximal CA3c mostly through superficial CA1 cells, while the activity of distal CA3a region and CA2 pyramidal neurons is mostly decreased [ 26 , 62 , 63 ]. At CA3c, interactions with hilar cell types and DG granule cells may be playing roles in shaping SWR initiation [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%